The effect of perceived organisational support on burnout among community health nurses in China: the mediating role of professional self‐concept. (26th February 2015) - Cao, Xiaoyi; Chen, Lin; Tian, Lang; Diao, Yongshu
Abstract : Aim: To examine the mediating effect of professional self‐concept on the association between perceived organisational support and burnout among community health nurses in Chengdu, China. Background: Burnout is a common phenomenon among nurses and previous studies have focused on work environmental factors contributing to burnout. Limited studies have examined the effects of perceived organisational support and professional self‐concept on burnout among community health nurses. Methods: This was a cross‐sectional study with 551 community health nurses in Chengdu, China, which included a two‐stage sampling method. Structural equation modelling was used to examine the relationships among perceived organisational support, professional self‐concept and burnout. Results: The final sample included 456 nurses (82.7%). Perceived organisational support was a significant positive direct predictor for professional self‐concept and a significant negative direct predictor for burnout. Professional self‐concept was a significant negative direct contributor to burnout. Professional self‐concept had a mediating effect on the relationship between perceived organisational support and burnout. Conclusions: Perceived organisational support may result in reduced burnout by facilitating the development of positive professional self‐concept. Implications for nursing management: Strategies such as establishing a supportive work environment and professional competence training may be effective methods for burnout prevention and management among community health nurses.